1996
DOI: 10.1021/jm960259l
|View full text |Cite
|
Sign up to set email alerts
|

Antipsoriatic Anthrones with Modulated Redox Properties. 3. 10-Thio-Substituted 1,8-Dihydroxy-9(10H)-anthracenones as Inhibitors of Keratinocyte Growth, 5-Lipoxygenase, and the Formation of 12(S)-HETE in Mouse Epidermis

Abstract: The synthesis of a series of 1,8-dihydroxy-9(10H)-anthracenones bearing sulfur-linked substituents in the 10-position is described. These compounds were evaluated for their ability to inhibit the growth of the human keratinocyte cell line HaCaT and the 5- and 12-lipoxygenase enzymes in bovine polymorphonuclear leukocytes and mouse epidermal homogenate, respectively. In addition, the following redox properties of the compounds were determined: reactivity against 2,2-diphenyl-1-picrylhydrazyl, generation of hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…This was assessed by the activity of LDH (lactate dehydrogenase) released into the culture medium, which is commonly used as an indicator of plasma membrane damage [9,38].…”
Section: Biological Assay Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was assessed by the activity of LDH (lactate dehydrogenase) released into the culture medium, which is commonly used as an indicator of plasma membrane damage [9,38].…”
Section: Biological Assay Methodsmentioning
confidence: 99%
“…The assay was performed as described [9,38]. HaCaT cells were incubated with the test compounds (2 mM) for 4 h at 37 C. Extracellular LDH activity was measured using the UV method with pyruvate and NADH and is expressed in mU/ml.…”
Section: Lactate Dehydrogenase Releasementioning
confidence: 99%
“…Moreover, the preliminary ESR studies revealed that the reduction power of anthracenones substituted with an electron-withdrawing group in the C-10 position is impeded, whereas that of 10-thio derivatives is increased. 16,17) The reaction undergoes a nucleophilic substitution at the 1 and 5 positions with the appropriate thiols in the presence of sodium methoxide and THF at room temperature or after reflux for 1 to 2 h to generate this structural class of anthraquinones. The mechanism for the reaction may be rationalized assuming that thiols are ionized by sodium methoxide as nucleophiles undergo nucleophilic substitution.…”
Section: Chemistrymentioning
confidence: 99%
“…Calibration was performed as described. 20) Log P values as a measure of lipophilicity are given in Table 1.…”
Section: 5-dichloro-9(10h)-anthracenone (2)mentioning
confidence: 99%